Self-Efficacy and Utilization of Prolanis Health Services for Type 2 Diabetes Mellitus Patients - iswatun, iswatun; Susanto, Joko; Umam, Khotibul; Hidaayah, Nur (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
The prevalence of type 2 Diabetes Mellitus (DM) continues to increase globally, including in Indonesia, causing a decrease in quality of life and the risk of serious complications. The Chronic Disease Management Program (Prolanis) is designed to improve disease management, but its utilization has not been optimal. Self-efficacy is a key factor in encouraging patient participation in health services. Objectives: This study aims to analyze the relationship between self-efficacy and the utilization of Prolanis health services in patients with type 2 diabetes mellitus. Specifically, the objectives of this study include identifying the level of self-efficacy of type 2 DM patients who are members of the Prolanis group and assessing the level of utilization of Prolanis health services by type 2 DM patients. Methods: The study was conducted using a cross-sectional approach at the Lamongan Health Center from March to May 2023. The study sample was 125 DM patients in the Prolanis group who were selected by accidental sampling. The research instrument used a general self-efficacy questionnaire and a questionnaire on utilizing the Prolanis health service system compiled by researchers from the results of a literature review and data analysis using the Spearman Rank test. The study results showed that the majority of respondents, 68%, had high self-efficacy, and 51.2% made good use of Prolanis health services. The results of the Spearman Rank test are p = 0.000 and r = 0.763, meaning that there is a relationship between self-efficacy and the utilization of Prolanis health services for type 2 DM patients. The correlation strength is strong and positive. The conclusion shows that high self-efficacy in type 2 DM patients tends to be better at utilizing Prolanis health services than low self-efficacy.